A dissociation in judgements of confidence in people with dandruff based on self‐reports compared to reports from other observers. (23rd May 2017) - Godbehere, A.; McDonald, L.; Baines, F.; Sutherland, C. A. M.; Andrews, T. J.
Abstract: Objective: It is not clear how well evaluations made by other people correspond with self‐evaluations of esteem or confidence. To address this question, we compared measurements of confidence in participants with and without dandruff. Methods: Participants with dandruff were significantly different from healthy control participants on a quality of life measure of scalp dermatitis, but not on self‐evaluations of esteem or confidence. To determine whether there were differences in the evaluation of confidence by others, both groups of participants were videoed while they prepared for or gave a presentation in an interview scenario. Results: Raters, who were unfamiliar with the identities of the participants, evaluated confidence from the muted videos. In contrast to their self‐evaluations, male participants with dandruff were rated as having lower confidence compared to participants who reported a healthy scalp. Conclusions: These findings reveal a difference between explicit and implicit measures of self‐esteem in men compared to women with dandruff.